Age, socioeconomic patterns and regional variations in grip strength among older adults (50+) in India: Evidence from WHO's Study on Global Ageing and Adult Health (SAGE). (May 2018) - Arokiasamy, P.; Selvamani, Y.
Highlights: Socioeconomic status predicts grip strength among older adults, especially in the early years. Socioeconomic patterns of grip strength differ considerably by gender. Socioeconomic convergence of grip strength in older ages is notable. Evidence of considerable variation in grip strength across states of India is evident. Edentulism and poor self-rated health were strongly associated with grip strength. Abstract: Background: Muscle strength, measured as grip strength is a potential marker of bodily function and sarcopaenia. Yet, not much is known about its patterns and correlates among older population in India. This study assesses the age and socioeconomic patterns and state variations in grip strength among older adults (50+) in India. Methods: A cross-sectional and nationally representative data from the first wave of WHO's Study on global Ageing and Adult Health (SAGE) −2007 ( n = 6262) was used. Multivariable linear regression analyses were used to understand the regional variations and association of socioeconomic status and general health with grip strength, adjusting for anthropometric and demographic confounders. Results: Socioeconomic status has a significant association with grip strength. Moreover, the association between wealth quintile and grip strength was highly significant. Further, the socioeconomic differences in grip strength narrowed in older ages, especially among men, supporting the convergence of health inequality hypothesis. Notable differences were observed in grip strength across selected states of India. Poor self-rated health was negatively associated with grip strength. Edentulism in men was associated with reduced grip strength. Conclusion: This study has contributed to a better understanding of significant social and regional inequalities in grip strength among older population in India. State-specific and subgroup level interventions are important to improve the physical functioning of the growing older population in India.